Neuromuscular regulation in zebrafish by a large AAA+ ATPase/ubiquitin ligase, mysterin/RNF213 - Kotani, Yuri (Sci Rep, 2015)
Mysterin (also known as RNF213) is a huge intracellular protein with two AAA+ ATPase modules and a RING finger ubiquitin ligase domain. Mysterin was originally isolated as a significant risk factor for the cryptogenic cerebrovascular disorder moyamoya disease, and was found to be involved in physiological angiogenesis in zebrafish. However, the function and the physiological significance of mysterin in other than blood vessels remain largely unknown, although mysterin is ubiquitously expressed in animal tissues. In this study, we performed antisense-mediated suppression of a mysterin orthologue in zebrafish larvae and revealed that mysterin-deficient larvae showed significant reduction in fast myofibrils and immature projection of primary motoneurons, leading to severe motor deficits. Fast muscle-specific restoration of mysterin expression cancelled these phenotypes, and interestingly both AAA+ ATPase and ubiquitin ligase activities of mysterin were indispensable for proper fast muscle formation, demonstrating an essential role of mysterin and its enzymatic activities in the neuromuscular regulation in zebrafish.